Peranan Perangkat Desa dalam Penyelenggaraan Pendidikan Anak Usia Dini di Desa Emplak Kalipucang - Intan Permatasari; Fitri Fajriyatussa’adah; Asri Sawalianti; Rosita Wulandari (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
This research aims to find out the role of the village in implementing early childhood education at RA Al-Huda Emplak Kalipucang. The method in this research uses a descriptive method with a qualitative approach. This research is based on a natural setting as a direct data source and researchers are the key instrument for knowing changes before and after the establishment of early childhood education institutions in Emplak Village, Kalipucang District. The results of the research show that the role of village officials in organizing early childhood education at RA Al-Huda Emplak Kalipucang is quite important. This is proven by the facilities provided by village officials to support learning, assist school planning to achieve the goal of providing quality early childhood education, and educators are supported to continue their education in accordance with their scientific fields. Therefore, the role of village officials is very important to support the implementation of educational institutions in Emplak Kalipucang Village.